Finite element method analysis of a linear friction welded Ti6Al4V alloy - Unal, Engin; Yalcin, Harun (Walter de Gruyter Gmbh, 2023)
Linear friction welding (LFW), which is generally used in blisk construction in aviation and space industries, is especially used to reduce costs, extend the life of materials working in hot environments, lighten engine weight, etc. The method, which is a solid state welding, achieves a high welding structure in metal and alloy materials. It can also be applied to different material combinations such as titanium alloys, superalloys, steel, aluminum, nickel, and copper. This study, which was carried out in order to provide lower cost and less raw material consumption in the welding of titanium alloys, reveals the necessity of the LFW method. In this study, the temperature change, oscillation amplitude, and oscillation frequency of the Ti6Al4V couple were investigated using the LFW method using finite elements. In the transient thermal analysis, it was observed that the temperature produced by applying Ti6Al4V welding parameters exceeded the glass transition temperature of the material.
Keywords: ANSYS; finite element method; linear friction welding; processing parameters; titanium alloy